2008
DOI: 10.1001/archotol.134.7.757
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Interrater and Intrarater Reliability in the Endoscopic Evaluation of Velopharyngeal Insufficiency

Abstract: Objective: To explore interrater and intrarater reliability (R inter and R intra , respectively) of a standardized scale applied to nasoendoscopic assessment of velopharyngeal (VP) function, across multiple centers. Design: Multicenter blinded R inter and R intra study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 18 publications
2
47
0
4
Order By: Relevance
“…The interpretation of imaging techniques, such as (video)fluorography and (video)endoscopy, is subjective 30,31 . Skolnick and Cohn 31 state that the conduct and interpretation of videofluoroscopic studies are as much an art as a science.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The interpretation of imaging techniques, such as (video)fluorography and (video)endoscopy, is subjective 30,31 . Skolnick and Cohn 31 state that the conduct and interpretation of videofluoroscopic studies are as much an art as a science.…”
Section: Discussionmentioning
confidence: 99%
“…Skolnick and Cohn 31 state that the conduct and interpretation of videofluoroscopic studies are as much an art as a science. Sie et al 30 argue that in the absence of an objective, quantifiable measure of VP function, it is important to understand the reliability of clinical tools used in the treatment of patients with VPI. In their study on reliability in the endoscopic evaluation of VPI, they found that the inter-observer reliability of rating qualitative characteristics is variable and is too low to be used for comparing subjects across centres.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Items rated in this scale include right and left lateral pharyngeal wall movement, right and left palate movement and elevation, posterior pharyngeal wall movement, and estimate of gap size. Given that endoscopy cannot absolutely measure the distance of movements, the scale system has some limitations [ 17 ] . The clinician should position the scope in the nasopharynx adjacent to the vomer bone to view velar function.…”
Section: Performing the Exammentioning
confidence: 99%